Two-Dimensional Transition Metal Oxide and Hydroxide-Based Hierarchical Architectures for Advanced Supercapacitor Materials - Guan, Meili; Wang, Qiuwan; Zhang, Xuan; Bao, Jian; Gong, Xuezhong; Liu, Youwen (Frontiers in Chemistry, 2020)
The supercapacitor has been widely seen as one of the most promising emerging energy storage devices, by which electricity is converted from chemical energy and stored. Two-dimensional (2D) metal oxides/hydroxides (TMOs/TMHs) are revolutionizing the design of high-performance supercapacitors because of their high theoretical specific capacitance, abundance of electrochemically active sites, and feasibility for assembly in hierarchical structures by integrating with graphitic carbon, conductive polymers, and so on. The hierarchical structures achieved can not only overcome the limitations of using a single material but also bring new breakthroughs in performance. In this article, the research progress on 2D TMOs/TMHs and their use in hierarchical structures as supercapacitor materials are reviewed, including the evolution of supercapacitor materials, the configurations of hierarchical structures, the electrical properties regulated, and the existence of advantages and drawbacks. Finally, a perspective covering directions and challenges related to the development of supercapacitor materials is provided.